Psychotropic drug concentrations and clinical outcomes in children and adolescents: a systematic review. Issue 7 (2nd July 2020) - Kloosterboer, Sanne M.; Vierhout, Denise; Stojanova, Jana; Egberts, Karin M.; Gerlach, Manfred; Dieleman, Gwen C.; Hillegers, Manon H. J.; Passe, Kimberly M.; Gelder, Teun van; Dierckx, Bram; Koch, Birgit C. P.
ABSTRACT: Introduction: The use of psychotropic drugs in children and adolescents is widespread but associated with suboptimal treatment effects. Therapeutic drug monitoring (TDM) can improve safety of psychotropic drugs in children and adolescents but is not routinely performed. A major reason is that the relationship between drug concentrations and effects is not well known. Areas covered: This systematic review evaluated studies assessing the relationship between psychotropic drug concentrations and clinical outcomes in children and adolescents, including antipsychotics, psychostimulants, alpha-agonists, antidepressants, and mood-stabilizers. PRISMA guidelines were used and a quality assessment of the retrieved studies was performed. Sixty-seven eligible studies involving 24 psychotropic drugs were identified from 9, 298 records. The findings were generally heterogeneous and the majority of all retrieved studies were not of sufficient quality. For 11 psychotropic drugs, a relationship between drug concentrations and side-effects and/or effectiveness was evidenced in reasonably reported and executed studies, but these findings were barely replicated. Expert opinion: In order to better support routine TDM in child- and adolescent psychiatry, future work must improve in aspects of study design, execution and reporting to demonstrate drug concentration-effect relationships. The quality criteria proposed in this work can guide future TDM research. Systematic review protocol and registration PROSPERO CRD42018084159